COVID-19 in Indonesia: Is There a Shift from Pandemic to Endemic? - Hanifah, Laily; Siregar, Kemal N (UI Scholars Hub, 2022)
The world is still facing the Coronavirus Disease 2019 (COVID-19) pandemic, and the current challenge is the epidemic, which was thought to have become endemic, but it seems far from that. This article describe the recent progress of the COVID-19 globally, including in Indonesia, and what should be done towards building community health resilience. Each day, more than 500,000 new cases are being detected worldwide. This condition shows that the present pandemic is not over and still requires global vigilance. The challenge faced by the world, and Indonesia, is to develop resilient communities as a prerequisite to controlling any future epidemic. This can be achieved by adopting five strategies: strengthen and promote access to public health and social services, promote health and wellness and disaster preparedness, expand communication and collaboration, engage at-risk individuals and activate programs to protect their health, and build social connectedness.